Odpowiedź :
A) 2*1-4=-2
B) 12-4*7=12-28=-16
C)-2*(-3,5)=7
D) 2*(-3)+4,4= -6+4,4=-1,6
E) -5*2,2-(-1)-11=-11+1-11=-21
B) 12-4*7=12-28=-16
C)-2*(-3,5)=7
D) 2*(-3)+4,4= -6+4,4=-1,6
E) -5*2,2-(-1)-11=-11+1-11=-21
a) 2x-4=
= 2•1-4=
= 2-4=-2
b) 12 - 4=
=12 - 4 • 7=
=12 - 28=
= -16
c)- 2y- 6=
=- 2 •(-3,5 )- 6=
=7 -6=
=1
d) 2x+y =
= 2•(-3)+4,4=
=6+4,4=
= 10,4
e) -5a-b-11=
=-5•2,2-(-1)-11=
=-11+1-11=
=-10-11=
=-21
daj naj proszę
= 2•1-4=
= 2-4=-2
b) 12 - 4=
=12 - 4 • 7=
=12 - 28=
= -16
c)- 2y- 6=
=- 2 •(-3,5 )- 6=
=7 -6=
=1
d) 2x+y =
= 2•(-3)+4,4=
=6+4,4=
= 10,4
e) -5a-b-11=
=-5•2,2-(-1)-11=
=-11+1-11=
=-10-11=
=-21
daj naj proszę